Localized public investment and agricultural performance in Malawi: An econometric approach - Mwabutwa, Chance (International Food Policy Research Institute, 2017)
Using panel data econometric techniques, this paper evaluates how public expenditure influences agricultural performance at the district level in Malawi by empirically estimating localized expenditure multipliers for the districts. The results of the analysis show that public expenditures in agriculture have generally positive but variable impacts on agricultural growth at the district level. The paper also finds that there are substantial differences in terms of fiscal multipliers among the districts: most of these multipliers lie below one, although some are above one, while a few are negative. These results confirm that increasing public expenditures in agriculture can yield modest but positive impacts on agricultural productivity. The realization of improved impacts partly depends on both enhancing the quality of public spending and improving the health of public finances across the districts of Malawi.